Gender Differences in the Creativity–Academic Achievement Relationship: A Study from China. (11th November 2018) - Zhang, Wenjing; Ren, Ping; Deng, Lifang
Abstract: This study investigated gender differences in the relationship between creativity and academic achievement. A sample of 1082 primary students participated in this study in Beijing, China. Their age ranged between 8 and 15 years old ( M = 10.41, SD = 0.99). Students' creativity was measured by the Chinese version of the Torrance Test of Creative Thinking Figural Form A, and academic achievement was based on students' self‐reported grades of last semester. Results revealed that there was a significantly positive relationship between creativity and academic achievement, ranging from r = .07 to r = .21. Gender differences regarding which aspects of creativity were related to academic achievement were also found. Plausible explanations and implications of the findings in creativity research and education are discussed.